Intracerebral hemorrhage following mild ARIA-H in an APOE ε2 carrier receiving lecanemab - Sung Ji; Michael Rosenbloom (Alzheimer’s Research & Therapy)
Abstract Objective Report a case of an apolipoprotein E (APOE)ε2 carrier receiving lecanemab who developed late onset intracerebral hemorrhage (ICH) following amyloid-related imaging abnormalities-hemorrhage (ARIA-H). Method We detail the history and neuroimaging findings of a 73-year-old male with Alzheimer’s disease (APOEε2/ε3 status) who developed ICH after mild ARIA-H and suffering a fall. Results The patient developed mild ARIA-H after his 13th infusion that was proceeded by left temporo-occipital hemorrhage following his 14th infusion. Discussion Although APOE ε2 is known to be protective against Alzheimer’s disease, it has also been shown to increase risk for hemorrhage with cerebral amyloid angiopathy. This case serves as an opportunity to examine the complex role that APOE ε2 plays in both protection against Alzheimer’s disease and contribution to increased hemorrhagic risk with lecanemab.